2011
DOI: 10.4028/www.scientific.net/amr.278.539
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations and Strengthening Mechanisms in Developing Co-Re-Based Alloys for Applications at + 100°C above Ni-Superalloys

Abstract: Abstract. Although Ni-base superalloys meet the gas turbine needs of today, they are used very close to their melting range. Demands for applications at higher temperatures are presently met partly through component cooling and application of thermal barrier coatings. However, this approach can not be sustained indefinitely unless the base metal melting temperature is also significantly increased. Rhenium addition can substantially increase the melting point in Co-base alloys and thereby provide a unique oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The oxy-fuel turbine is still under development and it is assumed that single crystal alloys will be used in the turbine. Current research has shown that single crystal alloys can handle up to 1000 • C [31,32].…”
Section: Conceptual Turbine Designmentioning
confidence: 99%
“…The oxy-fuel turbine is still under development and it is assumed that single crystal alloys will be used in the turbine. Current research has shown that single crystal alloys can handle up to 1000 • C [31,32].…”
Section: Conceptual Turbine Designmentioning
confidence: 99%
“…Figure 2 shows the Sovran and Klomp chart for the performance of a conical diffuser In SCOC-CC, the combustion outlet temperature was higher due to changing gas turbine working fluid and was set to 1400 C. This firing level exceeds the blade material limitations. The study assumed using high temperature material such as fourth generation single crystal alloys in manufacturing turbine blades [26,27]. Thus the stator metal temperature was set to 950 C, while the rotor metal temperature was set to 920 C. The metal temperature is a function of the material properties and cooling technique.…”
Section: Dimensionless Mass Flowmentioning
confidence: 99%
“…In SCOC-CC, the combustion outlet temperature was higher due to changing gas turbine working fluid and was set to 1400 C. This firing level exceeds the blade material limitations. The study assumed using high temperature material such as fourth generation single crystal alloys in manufacturing turbine blades [26,27]. Thus the stator metal temperature was set to 950 C, while the rotor metal temperature was set to 920 C. The metal temperature is a function of the material properties and cooling technique.…”
Section: Dimensionless Mass Flowmentioning
confidence: 99%